Pre-service Teachers’ Perception of the Benefits of Problem-solving and Strategies Used to Solve Mathematical Problems: A Case from some Colleges of Education in Ghana - Gyampoh, Samuel Amoh (Journal of Mathematical Pedagogy (JoMP), 2025)
The quality of pre-service mathematics teacher education depends greatly on their understanding of mathematical problem-solving and its pedagogy. This study investigates pre-service teachers’ perceptions of the benefits of problem-solving in mathematics and the strategies they employ to solve problems. A qualitative design was adopted, involving 30 randomly selected participants from three Colleges of Education in Ghana. Data were collected through semi-structured interviews, transcribed, and analyzed thematically. Findings reveal that participants possess substantial knowledge of the benefits of problem-solving, including developing critical thinking and understanding, fostering intellectual challenge, enhancing real-life application skills, achieving set goals, overcoming difficulties, and selecting appropriate strategies. The study also highlights the range of strategies used by pre-service teachers, such as visual representation, logical reasoning, and varied heuristic approaches. These insights underscore the need to strengthen problem-solving pedagogy in teacher preparation programs to enhance both mathematical understanding and teaching practice.